Chinese herbal medicines on cognitive function and activity of daily living in senior adults with Alzheimer's disease: a systematic review and meta-analysis - Yanjie Zhang; Kyoungmin Noh; Wook Song (Integrative Medicine Research)
Background: This systematic review was performed to investigate the effects of Chinese herbal nedicine (CHM) on cognitive function and activity of daily living (ADL) in individuals with Alzheimer's disease. Methods: Five electronic databases (Medline, Embase, Cinahl, PsycArticles, and CNKI) were searched from inception to January 2019. Randomized controlled trials (RCTs) assessing the effect of CHM on cognition and activity of daily living in adults with Alzheimer's disease were included. We pooled the effects size using the Comprehensive Meta-Analysis Software. Cochrane risk of bias tool was used to evaluate the study quality. Results: Twenty-five RCTs (1855 individuals with AD) were included in this review. Overall findings of this meta-analysis indicated that CHM improved the cognitive function (SMD = 0.66, 95% CI [0.44, 0.89], I2 = 77.9%, p < 0.001) and ADL (SMD = 0.38, 95% CI [0.25, 0.49], I2 = 35.3%, p < 0.001) compared with conventional drugs. No publication biases were observed on both cognitive function and ADL. Conclusion: CHM may have potential effects for improving cognitive function and ADL for individuals with AD compared with conventional drug therapies. However, the evidence is limited because of high risk of bias of the included trials. Keywords: Alzheimer's disease, Chinese herbal medicine, Cognitive function, Meta-analysis